ANALYSIS OF THE IMAGERY RELATING TO THE CARPE DIEM IDEA IN THE POEM “THE RUBAIYAT” - Safnidar Siahaan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
This research is presented to discuss about the imagery of the poetry entitled “The Rubaiyat”. The Rubaiyat is a poem in the 11th century written by a Persian poet named Omar Khayyam. One of the poets who had translated the poem